Where roots run deep: fostering youth environmental motivation through livelihoods in rural place-based education - Maksymkiw, Sophie, author; Balgopal, Meena, advisor; Newman, Greg, committee member; Mola, John, committee member (Colorado State University. Libraries, 2025)
As youth stare into the beast of climate change, it is important for them to be prepared and feel agentic in attacking the hurdles of climate change. Youth students will be among the most affected by climate change in the future, however, due to the current political state of the US and the lack in access to climate change curricular materials, teaching climate comes with a few challenges (especially in rural school districts). Additionally, youth in the US are less likely to be motivated to act on environmental issues in comparison to youth in other countries. To target student environmental science motivation in an intermountain west region of the US, we grounded this study in Situated Expectancy Value Theory where we investigated how values, identity, and expectations of success contribute to motivation. We designed a Place-Based Education (PBE) climate change module where students engaged with participatory science data framed around phenological changes that are occurring to their local bumble bees and plants. Students of two middle school teachers, one in a suburban school (n=56) and one in a rural school (n=42) implemented the module. To measure the effects of environmental motivation conferred by the module, students took pre and post surveys. We found that identity increased in suburban students and values decreased in rural students after interacting with the module. Motivation in rural students started out lower and ended lower in comparison to suburban students. These differences revealed that rural students should engage in community action following a PBE environmental to avoid potential disempowerment. Through environmental contextualization of the two populations, we found a difference in experiences, knowledge types, and differing scopes of powerlessness between the two teachers, highlighting how the rural region experiences the environment more directly, leading to an effect on their livelihoods. These results suggest that livelihood validation and community environmental actions as promising integrations to rural curricula.
Keywords: participatory science; place-based education; pollinators; phenology; livelihoods; plants